Can Ethical Leaders Enhance Knowledge Sharing? The Role of Psychological Capital and Anticipated Reciprocal Relationships - Anil Kumar Goswami; Rakesh Kumar Agrawal (American Business Review, 2023)
The aim of the paper is to empirically investigate the influence of ethical leadership and psychological capital on knowledge sharing in business organizations. Furthermore, the paper investigates the mediating role of psychological capital and moderating role of anticipated reciprocal relationships in the relationship of ethical leadership with knowledge sharing. The analysis has been conducted on data gathered from 248 members of information technology (IT) companies by making use of survey questionnaire. Hypotheses are tested by analysing the data using structural equation modelling (SEM) and PROCESS macro. The study found that ethical leadership and psychological capital have positive effect on knowledge sharing. Ethical leadership also impacts psychological capital positively. Further, psychological capital acts as a mediator and anticipated reciprocal relationships act as moderator in the relationship of ethical leadership and knowledge sharing. This study establishes new antecedents of knowledge sharing, emphasizes the importance of ethical aspects of leadership in managing knowledge resources and enrich literature of Knowledge Management (KM), leadership, positive organizational behavior and human resources management. It further gives new perspectives to practitioners by recognizing the significance of ethical leadership, psychological capital and anticipated reciprocal relationships to enhance knowledge sharing. To the best of authors’ knowledge, this study is one of few initial studies to examine the linkages between ethical leadership, knowledge sharing and psychological capital as well as the role of anticipated reciprocal relationships therein.